Subordinate financialisation in Argentina and Brazil. Different patterns of dependence - Bona, Leandro Marcelo (2025)
This article contributes to the literature on dependency theory and subordinate financialisation in peripheral economies by examining the cases of Argentina and Brazil. Building upon the subordinate financialisation framework (Kaltenbrunner, Alami) and dependency theory (Marini), we analyse these nations' distinct experiences of international subordinate financialisation. Drawing on original evidence from constructed datasets of national and international accounts, we demonstrate that Brazil exhibits conventional drivers of subordinate financialisation—including household indebtedness, financialisation of non-financial corporations, and a developed banking system reliant on high interest rates to attract foreign capital. Conversely, Argentina manifests financial subordination through structural foreign currency illiquidity (at both national and internationallevels), dollarisation of savings, cyclical external indebtedness shaping real business cycles, and persistent capital flight.